Совершенствование налогообложения прибыли предприятий в Украине на основе оптимизации регулирующих бухгалтерско-налоговых разниц - Виецкая, О.В.; Мазур, Ю.А.; Кошик, Ю.В. (Економіка промисловості, 2012)
Досліджено оподаткування прибутку підприємств в Україні. Побудовано і реалізовано економіко-математичну модель впливу регулюючих бухгалтерсько-податкових різниць (податкової амортизації та інвестиційної податкової знижки) на інвестиційну діяльність підприємств і податкові надходження до бюджету. Обґрунтовано рекомендації щодо вдосконалення оподаткування прибутку підприємств в Україні. Ключові слова: оподаткування прибутку підприємств, бухгалтерсько-податкові різниці, амортизація, інвестиційна податкова знижка. Исследовано налогообложение прибыли предприятий в Украине. Построена и реализована экономико-математическая модель влияния регулирующих бухгалтерско-налоговых разниц (налоговой амортизации и инвестиционной налоговой скидки) на инвестиционную деятельность предприятий и налоговые поступления в бюджет. Обоснованы рекомендации по совершенствованию налогообложения прибыли предприятий в Украине. Ключевые слова: налогообложение прибыли предприятий, бухгалтерско-налоговые разницы, амортизация, инвестиционная налоговая скидка. Formation of corporate income tax in Ukraine was analyzed. Interaction between book and tax accounting of corporate income in Ukraine was researched. Basic changes in corporate income taxation introduced by the Tax Code were analyzed: introduction of recognizing revenues and expenses on accrual basis, the list of revenues and expenses, tax exemptions, system of tax depreciation etc. It was found that there are rules in domestic tax law that lead to book-tax differences and are useless from position of fiscal and regulatory function of taxation. In this regard, it was proposed to evaluate the use of regulating book-tax differences in Ukrainian legislation aimed at creating an investment basis of Ukrainian economy. Tax depreciation and investment tax credit were considered as book-tax differences. Economic and mathematical model of the effect of tax depreciation and investment tax credit on investment activity of enterprises and tax revenues was designed. Based on the analysis of the current system of corporate income tax in Ukraine, as well as the results of economic and mathematical modeling, the main directions aimed at improving corporate income taxation in Ukraine were set out. First, the corporate income tax system should be based on generally accepted accounting principles. Second, the number of book-tax differences should be minimized, and economically justified. Third, the rules for calculating tax depreciation as a source of book-tax differences should be divided into two components: the neutral one – in the form of tax depreciation for any enterprises, and the stimulating one – in the form of investment tax credit for profitable and investment active enterprises. Fourth, the choice of tax depreciation rate and investment tax credit rate should depend on the priorities of socio-economic development. Fifth, the optimal ratio of tax depreciation rates and investment tax credit under the current economic conditions in Ukraine is 22% and 70% respectively. Keywords: corporate income tax, book-tax differences, depreciation, investment tax credit.